The Role of Various out Patients Aural Toileting Procedures in the Treatment of Otomycosis - Chalabi, Yousif Ebrahim; San-Ahmed, Sarwat Tawfeq (Sulaimani Journal for Pure and Applied Sciences, 2010)
BACKGROUND: Otomycosis is not uncommon clinical problem requiring a long term treatment and has a recurrence tendency. Meticulous cleansing especially of anterior metal recess is the treatment mainstay. OBJECTIVES; to determine the clinical presentation and predisposing factors, compare the efficacy of aural toileting procedures and to assess the syringing role as a safe effective procedure for deep meatal recess debris removal. METHOD: A randomized prospective comparative study conducted on 91 patients (99 ears) in ENT consultation clinic- Sulaimani Teaching Hospital from April 2007 – November 2008. Patients were divided into two groups :group A underwent ear syringing and group B underwent dry suction cleansing. Data entry and analysis by software version 15 (2008) carried out (STATGRAPHICS) RESULTS: presenting symptoms were otalgia (94.5%), ear fullness (74.72%), itching (58.24%), hearing impairment (40.65%), otorrhea (20.87%) and headache (14.82%). Predisposing factors were ear moisture (94.5%), self cleansing habit (62.63%), ototopical agent overuse (36.26%) and dermatophytosis (19.78%). Dry cleaning showed complete debris removal in 31(63.26%) ears and incomplete removal in 18 (36.73%) ears while syringing showed complete removal in 38 (76%) ears and incomplete removal in 12 (24%) ears. Dry cleaning adverse effect was 37.37% compared to 12.12% in wet group. CONCLUSIONS; There was insignificant static differences (Chi-Squared p=0.3411) between the two regimens and both can be used for treatment. However, clinically gentle ear syringing is less time consuming, Less complicated and more meticulous in deep recess cleaning.
Keywords: Otomycosis Ear syringing; dry suction cleansing; anterior metal recess toilet AMR